Morphological Characteristics of Respiratory Tract in Children with Pneumonia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This study provides information on the bronchoscopy method of morphofunctional changes in pneumonia in children aged 28 days to 5 years.